2006
DOI: 10.1002/jbm.a.30870
|View full text |Cite
|
Sign up to set email alerts
|

An aligned nanofibrous collagen scaffold by electrospinning and its effects on in vitro fibroblast culture

Abstract: Fabrication of nanofibrous scaffolds with well-defined architecture mimicking native extracellular matrix analog has significant potentials for many specific tissue engineering and organs regeneration applications. The fabrication of aligned collagen nanofibrous scaffolds by electrospinning was described in this study. The structure and in vitro properties of these scaffolds were compared with a random collagen scaffold. All the collagen scaffolds were first crosslinked in glutaraldehyde vapor to enhance the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
220
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(231 citation statements)
references
References 26 publications
(38 reference statements)
10
220
0
1
Order By: Relevance
“…83 Schwan cells aligned along the PCL fibers and elongated along the orientation of the fibers, suggesting that the fibers guided the cell alignment and spreading. 144 Similar alignment has also been shown in fibroblasts 145 and endothelial cells. 146 Thus, in tissues where ordered cell alignment is necessary, fibers can be oriented by spinning the collector plate or with different void spaces.…”
Section: Cellular Interactionssupporting
confidence: 75%
“…83 Schwan cells aligned along the PCL fibers and elongated along the orientation of the fibers, suggesting that the fibers guided the cell alignment and spreading. 144 Similar alignment has also been shown in fibroblasts 145 and endothelial cells. 146 Thus, in tissues where ordered cell alignment is necessary, fibers can be oriented by spinning the collector plate or with different void spaces.…”
Section: Cellular Interactionssupporting
confidence: 75%
“…An assortment of natural polymers, such as the proteins collagen, elastin and silk fibroin, has been electrospun [25][26][27][28][29][30][31]. In addition, a wide variety of synthetic polymers such as polystyrene (PS), polycaprolactone (PCL), poly(methyl methacrylate) (PMMA) and poly(vinyl alcohol) (PVA) have been electrospun from solution.…”
Section: Introductionmentioning
confidence: 99%
“…16 Fibroblasts have also been shown to co-align and polarize along the axial direction of collagen fibers, whereas fibroblasts adhered to randomly oriented collagen fibers have an anisotropic orientation. 17 Perhaps even more significant, increased proliferation of fibroblasts adhered to aligned collagen scaffolds compared to the random scaffold was shown, with fibroblast morphology on aligned collagen comparing well with that seen in native tissues. 18 Elias et al showed that osteoblasts proliferate significantly more on a network of »100 nm diameter carbon fibers rather than on flat glass.…”
Section: Local Topology Effect On Cellsmentioning
confidence: 79%